2021
DOI: 10.12968/jowc.2021.30.12.1020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety and healing potential of a fibroin-aloe gel film for the treatment of diabetic foot ulcers

Abstract: Objective: This study aimed to develop a wound dressing prepared from the blending of silkworm fibroin and aloe gel extract for use in the treatment of diabetic foot ulcers (DFUs). Methods: Fibroin extracted from silkworm cocoons and aloe gel extract were dissolved in deionised water. pH levels were then adjusted with lactic acid solution. A simple casting technique was used to obtain the fibroin–aloe gel film. The surface morphology, hardness, flexibility and infrared spectrum of the sterilised film were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The cooperation of silk fibroin and aloe gel extract biomaterials has illustrated potential properties in promoting wound healing in in vitro and in vivo models, as well as in clinical trials. 12,13 Fibroin protein, comprising the silk cocoon of Bombyx mori, illustrates the remarkable biocompatibility to several cells and tissues because of its potent properties in the stimulation of the migration and proliferation of fibroblasts. 12,14 Furthermore, at the molecular level, silk fibroin accelerates signals, including AKT/mTOR and MAPK pathways extensively involved in cell migration and proliferation regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperation of silk fibroin and aloe gel extract biomaterials has illustrated potential properties in promoting wound healing in in vitro and in vivo models, as well as in clinical trials. 12,13 Fibroin protein, comprising the silk cocoon of Bombyx mori, illustrates the remarkable biocompatibility to several cells and tissues because of its potent properties in the stimulation of the migration and proliferation of fibroblasts. 12,14 Furthermore, at the molecular level, silk fibroin accelerates signals, including AKT/mTOR and MAPK pathways extensively involved in cell migration and proliferation regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that the blended fibroin/aloe gel extract film demonstrates potential healing effects, based on experimentations in vitro and in vivo in streptozotocin-induced diabetic rats, and clinical trials in diabetic foot ulcer patients. , Additionally, the γ-irradiated developed film enhanced the proliferation and migration of the healthy fibroblast cells. The presence of functional groups in the blended fibroin/aloe gel film, including amides (I, II, III), glucan units, pyranoside ring, and mannose, promotes tissue repair, but the underlying molecular mechanism is still unclear .…”
Section: Introductionmentioning
confidence: 99%
“…With very few trials, aloe vera had shown promising results in improving healing in DFU, but there are only few human trials[ 93 - 95 ] (Table 4 ) with small sample size, inadequate data, and low-level evidence. Worasakwutiphong et al [ 96 ] conducted a small pilot study by using blended silkworm fibroin and aloe gel extract for the dressing of five hard-to-heal DFU (Wagner grade 1). Spectroscopic analysis and tensile strength analysis showed favourable results.…”
Section: Aloe Veramentioning
confidence: 99%
“…Clinically, three DFU had a significant reduction in wound size and healed within 3 wk. The other two had healed by 4 wk[ 96 ].…”
Section: Aloe Veramentioning
confidence: 99%
“…e treatment of DF mainly includes medical treatment and surgical treatment. First, according to the situation of DF wounds, different methods of debridement and dressing change should be appropriately given to remove local bacteria or infected microorganisms to promote wound healing, and systemic antibiotic treatment should be given to patients at the same time [16,17]. After long-term conservative medical treatment, the wound will not heal for a long time and even the infection will be aggravated.…”
Section: Introductionmentioning
confidence: 99%